A Social Profile of Detroit: 1956. A Report of the Detroit Area Study of the University of Michigan - Martin, Yves (Relations industrielles / Industrial Relations, 1958)
The article reviews the booklet, "A Social Profile of Detroit: 1956. A Report of the Detroit Area Study of the University of Michigan," published by the Detroit Area Study, Department of Sociology and the Survey Research Center of the Institute for Social Research (83 pp.).